Correlation of Dyspepsia with the type of First Meal of the Day; Breakfast or Brunch: A Cross-Sectional Study from Karachi, Pakistan - Vishal Kumar Chandkai; Shahid Karim; Punhal Khan (Liaquat National Journal of Primary Care, 2023)
Background: Breakfast skipping is traditionally viewed as a bad habit. The customary choice for those who skip breakfast is brunch. Changes in gastrointestinal function are correlated with a range of dietary factors. Objective: To evaluate the correlation of the type of first meal of the day with dyspepsia among patients visiting gastroenterology clinics with dyspeptic symptoms. Methods: This cross-sectional study was conducted in the Department of Gastroenterology, Liaquat National Hospital from August 2021 to April 2022. Short-Form Leeds Dyspepsia Questionnaire was used to identify the presence of dyspepsia (SF-LDQ). Breakfast was defined as the meal consumed in the morning and any beverages or food taken in the morning before 11:00 a.m. regularly in a week. Data were analyzed using the statistical package SPSS version 21. Results: A total sample of 390 patients was analyzed in this study with median age and duration of symptoms of 35 (IQR=26- 42) years and 12 (IQR=8-24) months respectively. The frequency of breakfast skipping was 15.6%. The frequency of dyspeptic symptoms including indigestion, heartburn, regurgitation, and nausea was significantly higher among patients taking brunch as the first meal of the day than those who were having breakfast regularly. The frequency of dyspepsia was 75.1%. On univariate and multivariable analysis, the practice of consuming breakfast regularly was found to be associated with a lower risk of dyspepsia than those who were consuming brunch as the first meal of the day. Conclusion: The current study analyzed that type of first meal was significantly associated with dyspepsia. The frequency of dyspeptic symptoms was significantly higher among patients taking brunch at least once a week than patients who were regularly consuming breakfast.